Campaign Design For Plastic Waste Treatment Workshop In Bandung City - Magfirah Nugraheni, Andi; Widiatmoko Soewardikoen, Didit; Azhar, Hanif; Nur Hadiansyah, Mahendra (Sahabat Publikasi, 2024)
This research is entitled